Efeito do fortalecimento de músculos do membro superior e tronco sobre a cinemática e desempenho na tarefa de chute - Miguel Arcanjo de Assis (2013)
Introduction: During the instep kick movement in soccer, the mechanical energy generated or stored in upper body can be transferred to the lower limbs. In initial phase of the kick, the anterior muscles of the trunk and non-kick side contract eccentrically, absorbing and storing energy. In the following phases that energy stored is released, favoring the energy transference to the kicking leg. During instep kick, the anterior muscles and fasciae of the trunk and upper limb function as a continuous miofascial line of propagation force, storing and transmitting energy to the lower limb. An intervention capable of increasing the strength and stiffness of muscles and fasciae upper limb and trunk could favor the use of a pattern movement involving these segments. Objective: To investigate the effect of a strengthening program of upper limbs muscles and trunk muscles on the kinematics and performance of the maximum instep kick task. Materials and method: Twenty six male participants were randomly allocated into two groups of 13 participants (experimental and control). The experimental group performed three weekly sessions of arm and trunk muscles strengthening and practiced the instep kick during eight. The individuals of the control group practiced the instep kick three times per week and during eight weeks. Before and after the intervention period, the participants were subjected to three-dimensional kinematic assessment during the maximum instep kick speed and the ball velocity. For the statistical analysis, was extracted the angular displacement curves of all joints evaluated and angular velocity curves of hip and knee. To compare the curves obtained on the assessment and reassessment, confidence intervals (95% CI) were calculated for the differences between the values of the curves obtained in the evaluation and reevaluation, at each percentage of the kick. Mixed design analyses of variance with between-subject effect (experimental and control groups) and within-subject effect (pre- and post-training) were used to investigate the effect of strengthening program in kick performance variables: peak hip flexion velocity, peak knee flexion velocity, peak foot velocity and ball velocity. Results: In the experimental group, was found an increase in extension of the hip in 10-23% and increase in non-kick side rotation of the trunk in 20-43% of the kick. In addition, was found an increase in the hip extension velocity in 0-4% of the kick. In the control group, was found a reduction in the extension of the hip in 0-10% of the kick and a decrease in the knee flexion velocity in 3-10% of the kick. No effects were found on the variables related to the kick performance. Discussion and Conclusion: The higher non-kick side rotation of the trunk indicates a change in pursuit of increasing the efficiency of mechanism utilization (transference) of the force generated by the trunk muscles. The greater hip extension participates of miofascial oblique line stretching, resulting in greater energy absorption. These changes would be suggestive of a better use and distribution of energy along the kinetic chain during the instep kick. The changes found in kinematics after the strengthening were not sufficient to generate changes in variables related to instep kick performance. In the control group were also found changes in the hip and knee kinematics. However, these changes do not seem to be related to better use and distribution of energy along the kinetic chain.